On the interaction between theory, experiments, and simulation in developing practical learning control algorithms - Longman, Richard W. (Zielona Góra: Uniwersytet Zielonogórski)
Iterative learning control (ILC) develops controllers that iteratively adjust the command to a feedback control system in order to converge to zero tracking error following a specific desired trajectory. Unlike optimal control and other control methods, the iterations are made using the real world in place of a computer model.
Keywords: iterative learning control; ILC; 2D systems; learning transients